Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada PERUMDA Mual Nauli Kabupaten Tapanuli Tengah - Putri Andani; Rosmita Ambarita; Tiurlina Hasmawati Sihite (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of leadership style and work discipline on employee performance at PERUMDA Mual Nauli, Central Tapanuli Regency. This research uses a quantitative approach with an associative research type. The population consisted of 133 employees, with a sample of 55 respondents determined using the Slovin formula and incidental sampling technique. Data collection techniques included questionnaires, observations, and interviews. Data analysis was conducted using multiple linear regression with SPSS. The results show that partially, leadership style has a positive and significant effect on employee performance with a significance value of 0.010, while work discipline has a positive and significant effect with a significance value of 0.001. Simultaneously, leadership style and work discipline significantly affect employee performance with a significance value of 0.000. The coefficient of determination (R²) of 0.254 indicates that 25.4% of the variation in employee performance can be explained by these variables, while the remaining 74.6% is influenced by other factors outside the study. Work discipline is the most dominant variable affecting employee performance.